Social isolation causes downregulation of immune and stress response genes and behavioural changes in a social insect. Issue 10 (9th April 2021) - Scharf, Inon; Stoldt, Marah; Libbrecht, Romain; Höpfner, Anna Lena; Jongepier, Evelien; Kever, Marion; Foitzik, Susanne
Abstract: Humans and other social mammals experience isolation from their group as stressful, triggering behavioural and physiological anomalies that reduce fitness. While social isolation has been intensely studied in social mammals, it is less clear how social insects, which evolved sociality independently, respond to isolation. Here we examined whether the typical mammalian responses to social isolation, e.g., an impaired ability to interact socially and immune suppression are also found in social insects. We studied the consequences of social isolation on behaviour and brain gene expression in the ant Temnothorax nylanderi . Following isolation, workers interacted moderately less with adult nestmates, increased the duration of brood contact, and reduced the time spent self‐grooming, an important sanitary behaviour. Our brain transcriptome analysis revealed that only a few behaviour‐related genes had altered their expression with isolation time. Rather, many genes linked to immune system functioning and stress response had been downregulated. This probably sensitizes isolated individuals to various stressors, in particular because isolated workers exhibit reduced sanitary behaviour. We provide evidence of the diverse consequences of social isolation in social insects, some of which resemble those found in social mammals, suggesting a general link between social well‐being, stress tolerance, and immune competence in social animals.